2023
DOI: 10.3390/brainsci13020173
|View full text |Cite
|
Sign up to set email alerts
|

Benzodiazepines and Mood Stabilizers in Schizophrenia Patients Treated with Oral versus Long-Acting Injectable Antipsychotics—An Observational Study

Abstract: Schizophrenia is a chronic, invalidating, and polymorphic disease, characterized by relapses and remission periods. The main treatment option in schizophrenia are antipsychotics, administered as an oral or as a long-acting injectable (LAI) formulation. Although international guidelines rarely recommend it, mood stabilizers (MS) and/or benzodiazepines (BZD) are frequently prescribed as adjunctive therapy in schizophrenia patients for various reasons. This is an observational, cross-sectional study including sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…The frequency of AP use was 67-98.8% in schizophrenia patients in these studies [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. Most patients (52.3% to 90.9%) were on AP monotherapy [28][29][30][31]34,38,[40][41][42][43][44][45][46][47][48][49][50][51][52], except for five studies [27,[53][54][55][56]. Monotherapy AP prescription generally showed an upward trend over the years [38], particularly for second-generation AP (SGA) monotherapy [43].…”
Section: Antipsychotic Prescription Trends and Clinical Correlatesmentioning
confidence: 78%
See 1 more Smart Citation
“…The frequency of AP use was 67-98.8% in schizophrenia patients in these studies [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. Most patients (52.3% to 90.9%) were on AP monotherapy [28][29][30][31]34,38,[40][41][42][43][44][45][46][47][48][49][50][51][52], except for five studies [27,[53][54][55][56]. Monotherapy AP prescription generally showed an upward trend over the years [38], particularly for second-generation AP (SGA) monotherapy [43].…”
Section: Antipsychotic Prescription Trends and Clinical Correlatesmentioning
confidence: 78%
“…Monotherapy AP prescription generally showed an upward trend over the years [38], particularly for second-generation AP (SGA) monotherapy [43]. Monotherapy is generally more frequent in patients receiving SGA [29,40,47,[56][57][58], particularly those initiated on olanzapine [53]. Nonetheless, there were several earlier studies reporting higher rates of first-generation AP (FGA) as compared to SGA monotherapy [31,45,50,54,59,60].…”
Section: Antipsychotic Prescription Trends and Clinical Correlatesmentioning
confidence: 99%
“…The current study demonstrated that the use of sedative-hypnotics at a low dosage is linked to a substantial decrease in both all-cause and CVD mortality among individuals diagnosed with OAS, displaying HRs of 0.855 and 0.685, respectively. In the treatment of schizophrenia, benzodiazepines are commonly prescribed alongside antipsychotic medications to alleviate symptoms of anxiety, sleep disorders, agitation, and antipsychotic-related side effects [ 31 , 32 , 33 ]. Approximately 20% of OAS were prescribed benzodiazepines in Asia [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data suggest that dose-dependent toxicity was greatest in the case of chlorpromazine, followed by olanzapine, clozapine, and quetiapine. 79 In addition, medication frequently used as concomitant treatment in schizophrenia, such as benzodiazepines or mood stabilizers, 78 may supplementarily increase the risk of neutropenia or agranulocytosis (carbamazepine, for instance, has a neutropenia risk of 1 in 200 patients). 75 Given the fact that a multitude of other nonpsychotropic drugs (such as antihypertensives, analgesics, diuretics, antimicrobials, etc.)…”
Section: Discussionmentioning
confidence: 99%